2001
DOI: 10.1063/1.1331337
|View full text |Cite
|
Sign up to set email alerts
|

Compressional acoustic wave generation in microdroplets of water in contact with quartz crystal resonators

Abstract: Resonating quartz crystals can be used for sensing liquid properties by completely immersing one side of the crystal in a bulk liquid. The in-plane shearing motion of the crystal generates shear waves which are damped by a viscous liquid. Thus only a thin layer of fluid characterised by the penetration depth of the acoustic wave is sensed by a thickness shear mode resonator. Previous studies have shown that the finite lateral extent of the crystal results in the generation of compressional waves, which may cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 14 publications
3
35
0
Order By: Relevance
“…The reflective wave interacts with the emitting wave constructively and destructively, resulting in resonant spikes. Each spike appears at an incremental film thickness that is multiples of the half wave length of the acoustic wave in liquid [17,35,8,7,9]. The longitudinal wave creates the spikes on the resonant frequency shift (Fig.…”
Section: Longitudinal Mode and Spikes On The Resonant Frequency Shiftmentioning
confidence: 96%
See 1 more Smart Citation
“…The reflective wave interacts with the emitting wave constructively and destructively, resulting in resonant spikes. Each spike appears at an incremental film thickness that is multiples of the half wave length of the acoustic wave in liquid [17,35,8,7,9]. The longitudinal wave creates the spikes on the resonant frequency shift (Fig.…”
Section: Longitudinal Mode and Spikes On The Resonant Frequency Shiftmentioning
confidence: 96%
“…[2,3,5,4,6]. A few investigations have shown that evaporation kinetics of pure [7][8][9] and complex fluids including suspensions [11,10] and polymer solutions [12] can also be measured by crystal resonators. However, theoretical modeling and data interpretation on multi-component systems are only at the beginning stage.…”
Section: Introductionmentioning
confidence: 98%
“…Quartz crystal resonators (QCRs) are commercially available and commonly used in the microelectronics industry. Routinely, resonators have been used as ultra-sensitive mass detectors, and are typically referred to as quartz crystal microbalances [4]. We demonstrate the ability of compact, reliable quartz crystal resonators to remove nonspecific binding, and improve fluorescent biosensor signal accuracy.…”
Section: Introductionmentioning
confidence: 98%
“…in which r e is the radius of the electrode, K is the maximum sensitivity at the center of the resonator that can be deduced from the experiment on covering the electrode completely with a liquid of known density and viscosity, and β defines the sensitivity dependence on r (Figure 1b), which was empirically decided as 2-2.15 [30,31]. Different from a QCM entirely covered with one liquid (Equations (5) and (6)), sensitivity S is important when measuring the position of the moving boundary of the droplet and a medium driven by EWOD.…”
Section: Methodsmentioning
confidence: 99%